On the Study of Pseudo 𝒮-Asymptotically Periodic Mild Solutions for a Class of Neutral Fractional Delayed Evolution Equations - Naceur Chegloufa; Belkacem Chaouchi; Marko Kostić; Wei-Shih Du (Axioms, 2023)
The goal of this paper is to investigate the existence and uniqueness of pseudo <semantics>S</semantics>-asymptotically periodic mild solutions for a class of neutral fractional evolution equations with finite delay. We essentially use the fractional powers of closed linear operators, the semigroup theory and some classical fixed point theorems. Furthermore, we provide an example to illustrate the applications of our abstract results.